The Relationship Between Intolerance of Uncertainty and Spiritual Well-Being Levels of COVID-19 Among Elderly: A Cross Sectional and Correlational Study - Sahin, Zumrut Akguen; Deniz, Muhammed; Akca, Duygu; Aras, Gulistan Uymaz; Dogan, Sedat (Sage Publications Inc, 2025)
The aim of this research is to relationship between intolerance of uncertainty and spiritual well-being levels during Covid-19 among elderly. This study was conducted with cross-sectional and corrational design. The research was conducted between January and June 2021 in Turkey's Eastern Anatolia Region. Introductory Information Form, Intolerance of Uncertainty Scale-Short Form (IUS), and Spirituality Index of Well-Being (SIWB) were used to collect data. The research was completed with 302 volunteers who met the following inclusion criteria. All participants belong to the Muslims. A negative significant correlation was found between IUS and SIWB; that is as the spirituality of the elderly individuals increased, the levels of intolerance of uncertainty decreased. It is recommended to identify the fears and intolerances of elderly individuals. For uncertainty, it is necessary to refine their spirituality. For this, it is recommended to organize spiritual education programs.
Keywords: COVID-19; elderly; intolerance of uncertainty; spirituality